2008
DOI: 10.1109/tdmr.2008.2002493
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Electrical Characteristics of the Copper-Metallized SPDT GaAs Switches at Elevated Temperatures

Abstract: Copper-metallized AlGaAs/InGaAs pseudomophic high-electron mobility transistor single-pole-double-throw (SPDT) switches utilizing platinum (Pt, 70 nm) as the diffusion barrier have been studied and demonstrated. As compared with the Au-metallized switches, the Cu-metallized SPDT switches exhibited comparable performance with insertion loss less than 0.5 dB, return loss larger than 20 dB, isolation larger than 35 dB, and the input power for 1-dB compression (input P 1 dB) of 28.3 dBm at 2.5 GHz. In order to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In order to extend the electrical measurement capability, the semiconductor parameter analyzer Agilent 4156 C was connected to the AFM system. 34 Figure 3 shows schematically the setup for electrical interference measurement in this work. Pad V 2 of the PSW array was connected to ground as a zero-voltage reference point, while pad V 1 was connected to the voltage source of the Agilent 4156 C through the AFM tip, from which a voltage changing from −6 V ∼ 6 V with an incremental of 50 mV was applied.…”
Section: Methodsmentioning
confidence: 99%
“…In order to extend the electrical measurement capability, the semiconductor parameter analyzer Agilent 4156 C was connected to the AFM system. 34 Figure 3 shows schematically the setup for electrical interference measurement in this work. Pad V 2 of the PSW array was connected to ground as a zero-voltage reference point, while pad V 1 was connected to the voltage source of the Agilent 4156 C through the AFM tip, from which a voltage changing from −6 V ∼ 6 V with an incremental of 50 mV was applied.…”
Section: Methodsmentioning
confidence: 99%
“…The measurement setup can be found elsewhere. 5) Figure 1 demonstrates a typical nanoscale I-V characteristic of ALD HfO 2 measured by conductive atomic force microscopy (CAFM). Three conduction regions can be clearly observed.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have been realized on thin SiO 2 films on Si substrates using this technique. [2][3][4][5][6] We can mention the pioneering works of Porti et al 2,3 and Wu et al 4,5 Both authors have shown that oxide degradation exhibits two aspects. First, an electrical aspect, where an important leakage current is measured after the application of an electrical stress.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Wu et al have carried out their experiment under vacuum and, in these conditions, were the only ones to propose time-to-breakdown distributions using a Weibull representation. 5 Sire et al 7 also preferred C-AFM measurements under vacuum and they could investigate the statistics of electrical breakdown field of HfO 2 and SiO 2 thin films, presented in the form of Weibull plots. We note nevertheless that the current range under study by Sire et al ($10 2 nA) was 3 decades higher than those explored by Porti et al, Wu et al, and Hourani et al, whose studies were limited to about 100 pA. That is to say that Sire et al examined hard-breakdown mechanisms whereas the other authors focused on reversible degradation processes.…”
Section: Introductionmentioning
confidence: 99%